IMPLEMENTATION OF LOW-CLASS DISTANCE LEARNING (PJJ) AT SD NEGERI IV SAMARANG WITH THE OBJECTIVE OF MAINTAINING QUALITY OF LEARNING - Dani Gunawan; Elga Nadia Khairunnisa; Eko Fajar Suryaningrat; Tetep (Journal Civics And Social Studies, 2022)
The quality of learning is determined by learning activities. This research aims to determine the implementation of distance learning (PJJ) for lower classes at SDN IV Samarang with the aim of maintaining the quality of learning, including: 1. To find out learning planning; 2. To find out the implementation of learning; 3. To find out learning evaluation. The benefit of this research is to increase scientific insight and a clearer theoretical/conceptual framework regarding the implementation of distance learning with the aim of maintaining the quality of learning. The research method used in this research is a qualitative research method with document analysis research type. Participants were lower grade teachers, lower grade students, and parents of lower grade students. Data collection was carried out by analyzing documents, observations and interviews. Data analysis/processing is carried out by describing the state of the content/material, and looking for a presentation of the quality of learning through the learning outcomes of lower class students in the form of pie charts in the implementation of distance learning. Based on the results of research carried out by researchers, it can be concluded that: 1. The learning planning that was made before carrying out learning activities in PJJ was very good, this is proven by the learning planning that meets the four elements that must be present in learning planning, namely; (1) there are goals that must be achieved, (2) there are strategies to achieve the goals, (3) resources that can support and, (4) implementation of each decision. 2. Implementation of distance learning, for the successful implementation of learning is good enough based on the learning components that have been implemented and are interrelated, including: (1) teachers, (2) students, (3) learning materials, (4) learning methods, ( 5) learning media, and (6) learning evaluation. 3. Evaluation of distance learning has been sufficiently implemented in involving five evaluation principles and elements including schools, parents, the environment and society at large. As well as learning results which are shown with a score of 0 – 50, the percentage of Thematic, Mathematics and B. Sundanese scores obtained a percentage of 42%.